Factors Associated With Helicobacter Pylori Infection Among School-Aged Children From a High Prevalence Area in Vietnam - Thai Hoang Che; Thai Hoang Che; Tu Cam Nguyen; Vy Ngoc Thao Vu; Hiep Thanh Nguyen; Dung Thi Phuong Hoang; Xuan Minh Ngo; Dinh Quang Truong; Patrick Bontems; Annie Robert; Phuong Ngoc Van Nguyen (Frontiers Media S.A., 2023)
Objectives: The study aimed to identify prevalence of H. pylori infection and associated risk factors among pupils of Ho Chi Minh city (HCMC).Methods: A total of 1,476 pupils aged 6-15 years were enrolled in this cross-sectional study using multiple-stage sampling method. Infection status was assessed using stool antigen-test. A questionnaire was used to obtain socio-demographic, behavioral, and environmental factors. Logistic regression was performed to assess possible factors related to the infection.Results: Of the 1,409 children included in the analysis, 49.2% were male and 95.8% were of Kinh ethnicity. About 43.5% of parents completed college or university. The overall prevalence of H. pylori was 87.7%. Infrequency of handwashing with soap after toilet, the use of only water to clean after toilet, crowded living areas, larger family size, and younger age were independently contributing to an increased prevalence of H. pylori.Conclusion:H. pylori infection is highly prevalent in HCMC, and is associated with poor hygienic practices, crowded living areas, larger family size, and younger age. These findings highlight the importance of fecal-oral route and the attribution of crowded living conditions to the spreading of H. pylori in HCMC. Therefore, preventive programs should be set up with a focus on education of hygiene practices, and oriented to those living in crowded conditions.